Functional biogeography of herbaceous assemblages along edaphic and climatic gradients in Amazonian forests - Figueiredo, Fernando O. G.; Moulatlet, Gabriel M.; Zuquim, Gabriela; Emilio, Thaise; Tuomisto, Hanna; Silveira, Marcos; Rodriques, Domingos; Costa, Flávia R.C. (FapUNIFESP (SciELO), 2026)
Soil, topography, and climate have been identified as strong drivers of functional composition turnover of plant communities, setting the dominant (“optimal”) community weighted mean (CWM) trait values. These same environmental factors may also affect disturbance regimes (e.g., the effect of soil fertility increasing tree turnover rates) as they create high-luminosity patches within dense canopy forest, promoting trait diversity, i.e. variance of the mean community trait values within and among communities. We analysed the drivers of functional trait turnover within and among 451 Zingiberales’ assemblages across Brazilian Amazonia, based on leaf mass per area (LMA), plant maximum height and seed size of 192 species. We detected functional turnover of the dominant assemblage trait values (given by the CWM) towards lower assemblage mean values of LMA, height and seed size, as soil fertility increased (higher sum of exchangeable bases) and local environments became wetter (bottomlands), in accordance with the expectations of the fast-slow growth trade-off along the whole-plant economic spectrum. Variability in seed size and plant height within assemblages increased towards lower topographic positions and low-nutrient soils, and the variance around dominant height and seed size values among assemblages increased towards bottomlands and regions with more seasonal climate. We conclude that, while soil and topography promote the filtering of a predictable functional composition, climate mostly promoted within and among-assemblage functional variance. Thus, it may be difficult to predict the effects of climate change based solely on the mean functional structure of Amazonian understory communities.